Mathematical modelling and optimization of processes of operation of radio-electronic systems of air courts - Мачалин, И. A.; Ткалич, О. П. (Problems of Informatization and Control, 2007)
Mathematical models of technical operation of radio-electronic systems on the basis of the sjemi-Markovian casual processes are considered. Parameters and criteria of optimization of periodicity of maintenance service of systems are developed